2012
DOI: 10.1186/1756-9966-31-4
|View full text |Cite
|
Sign up to set email alerts
|

Determination of SGK1 mRNA in non-small cell lung cancer samples underlines high expression in squamous cell carcinomas

Abstract: BackgroundLung cancer represents the most frequent cause of death for cancer. In non-small cell lung cancer (NSCLC), which accounts for the vast majority of this disease, only early detection and treatment, when possible, may significantly affect patient's prognosis. An important role in NSCLC malignancy is attributed to the signal transduction pathways involving PI3Kinase, with consequent activation of the AKT family factors. The serum and glucocorticoid kinase (SGK) factors, which share high structural and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 31 publications
2
52
0
1
Order By: Relevance
“…Given that Sgk1 expression in NSCLC patient samples significantly correlates with cancer malignancy and is thus considered a worse prognostic indicator [13], the in vivo use of a small molecule able to inhibit selectively Sgk1 kinase activity can specifically hit cancer cells, contemporarily sparing normal cells, characterized by a modest expression of the kinase Sgk1. On the other hand, the sometimes ambiguous results described for the clinical use of Akt inhibitors in cancer therapy [37,38], recently attributed to the high expression of Sgk3 [26],can carve out a peculiar role for Sgk inhibitors in blocking the Ras/PI3K/PTEN/Akt(Sgk)/mTOR pathway in specific neoplastic phenotypes [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that Sgk1 expression in NSCLC patient samples significantly correlates with cancer malignancy and is thus considered a worse prognostic indicator [13], the in vivo use of a small molecule able to inhibit selectively Sgk1 kinase activity can specifically hit cancer cells, contemporarily sparing normal cells, characterized by a modest expression of the kinase Sgk1. On the other hand, the sometimes ambiguous results described for the clinical use of Akt inhibitors in cancer therapy [37,38], recently attributed to the high expression of Sgk3 [26],can carve out a peculiar role for Sgk inhibitors in blocking the Ras/PI3K/PTEN/Akt(Sgk)/mTOR pathway in specific neoplastic phenotypes [1].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the anti-apoptotic function of Sgk1 suggests its possible involvement in human carcinogenesis. Sgk1 increased expression has been found in human tumors, like prostate cancer [12] and non-small cell lung cancer of the squamous subtype, where Sgk1 mRNA level correlates with several clinical prognostic indicators [13]. Sgk1 knockout mice appear to be resistant to the chemical carcinogens used for the induction of colon cancer [14].…”
Section: Introductionmentioning
confidence: 99%
“…SGK1 is highly expressed in several tumor cells [4], such as colon cancer [4], myeloma [5], medulloblastoma [6], prostate cancer [7], ovarian tumors [8] and non-small cell lung cancer [9]. On the other hand, down-regulation of SGK1 in some tumors has been reported, including adenomatous polyposis coli (APC) [3,4,10].…”
Section: Introductionmentioning
confidence: 99%
“…SGK1 is regulated by insulin [22][23][24], IGF-1 [25], glucocorticoids [26] and IL-2 [27]. Increased SGK1 expression has been documented in several human tumors [19,[28][29][30]. It has been demonstrated that SGK1 regulates cell survival, proliferation and differentiation via phosphorylation of MDM2, which governs p53 stability and degradation [31].…”
mentioning
confidence: 99%